Precise Excision of the CAG Tract from the Huntingtin Gene by Cas9 Nickases - Dabrowska, Magdalena; Juzwa, Wojciech; Krzyzosiak, Wlodzimierz J.; Olejniczak, Marta (Frontiers in Neuroscience, 2018)
Huntington’s disease (HD) is a progressive autosomal dominant neurodegenerative disorder caused by the expansion of CAG repeats in the first exon of the huntingtin gene (HTT). The accumulation of polyglutamine-rich huntingtin proteins affects various cellular functions and causes selective degeneration of neurons in the striatum. Therapeutic strategies used to date to silence the expression of mutant HTT include antisense oligonucleotides, RNA interference-based approaches and, recently, genome editing with the CRISPR/Cas9 system. Here, we demonstrate that the CAG repeat tract can be precisely excised from the HTT gene with the use of the paired Cas9 nickase strategy. As a model, we used HD patient-derived fibroblasts with varied numbers of CAG repeats. The repeat excision inactivated the HTT gene and abrogated huntingtin synthesis in a CAG repeat length-independent manner. Because Cas9 nickases are known to be safe and specific, our approach provides an attractive treatment tool for HD that can be extended to other polyQ disorders.